Bahasa Indonesia : Bahasa Indonesia - khairani, afifahrani (LPPM Universitas Negeri Jakarta, 2022)
Abstract This research is motivated by the lack of media that can facilitate teachers in delivering subject matter, media that can be used repeatedly even outside of class hours. The purpose of this research is to design an ICARE-oriented learning video on acid-base material with the help of adobe after effects software that is valid based on the validity of material experts, media experts, practicality tests for teachers and students. The research method used is Research and Development (R&D) with the Borg and Gall development model which includes the stages (1) research and information gathering, (2) planning, (3) developing the initial form of the product, (4) practicality testing and student responses, (5) product revision. The initial field test was carried out at MAN 1 Pekanbaru on students of class XI MIPA 1. The results of the validation of media experts and material experts obtained a score of 86.25% with very valid criteria. The teacher practicality test got a result of 95.83% in the very practical category, and the student practicality test got a result of 85.93% in the very practical category.